João Gilberto Noll e a pomossexualidade - Placido, Carlos Eduardo de Araujo (Universidade Federal de São Carlos, 2015)
João Gilberto Noll is a Brazilian author known for composing autodiegetic narrators who are meandering and unstable, many of them are difficult to grasp sexually what makes them subjective and moveable. The novel to be analyzed here, Solidão Continental (2012), is not different in relation to the nollian traditional form, but in relation to his traditional narrative and a renewed scope of content present in it. Both its protagonist, João Bastos, as well as some of its deuteragonist characters have an erotic / sexual transience which is sharp and difficult to understand. They are fictional beings without a fixed and stagnant sexual category, i.e., their sexualities are transient (AUGÉ, 1994), disperse (DELEUZE, & GUATTARI, 1995) and fragmentary (BLANCHOT, 1990). This sexual vagueness is being called pomosexuality by the sexologists Carol Queen & Lawrence Schimel in their work: PoMoSexuals: Challenging Assumptions About Gender and Sexuality (1997). Therefore, the objective of this academic work is to examine how the composition of the nollian traditional narrator is built up with the most striking pomosexual features indicated by those sexologists through the narrative constructions in relation to its narrator (voice and manner) by Gérard Genette, focusing mainly on the following relationships of these narrative instances: narrator / protagonist, narrator/deuteragonist characters and protagonist/deuteragonist characters.
Keywords: Literatura brasileira; Noll, João Gilberto, 1946-; Pós-modernismo; Literatura brasileira - romance; Pomossexualidade; João Gilberto Noll; LINGUISTICA, LETRAS E ARTES::LETRAS